SELAMATKAN HIDUP DENGAN BANTUAN HIDUP DASAR DI GEREJA KATOLIK SANTA PERAWAN MARIA RATU - Nataprawira, Sari Mariyati Dewi; Andria Priyana; Louise Audrey Sukianto; Kasvana; Nikita Tan (Jurnal Serina Abdimas, 2025)
Sudden Cardiac Arrest (SCA) is a condition where the heart suddenly stops functioning, leading to a lack of cardiac hemodynamic throughout the body. This condition, caused by a loss heart’s electrical activity, mostly occurs in public places such as offices, church, and so on. Quick and proper treatment for this condtion can reduce the mortality rate of those who experience it. Providing basic life support is an emergency treatment method for SCA. This method can be performed by anyone who is trained. Because this condition can occurs anywhere, such as in a church, it is necessary to prove basic life support training to staff, officers, and youth in those locations. Catholic church St. Mary the Vurgin Queen serves over 3.000 church members in Kebayoran, South Jakarta. As a public facility, SCA can occurs among church members, whether they are participating in religious activities or activities that support religious activities. Therefore, it is important for church staff and youth to be equipped with the ability to recognize the signs of SCA and perform initial treatment before medical personnel arrive or the patient is taken to medical facilities. This activities involves providing training to church staff and youth on recognizing SCA and performing Cardiopulmonary Resuscitation (CPR). It it hoped that, after compliting this training, church staff and youth will be equipped to provide initial treatment for SCA. Sudden Cardiac Arrest (SCA) is a condition where the heart suddenly stops functioning, leading to a lack of cardiac hemodynamic throughout the body. This condition, caused by a loss heart’s electrical activity, mostly occurs in public places such as offices, church, and so on. Quick and proper treatment for this condtion can reduce the mortality rate of those who experience it. Providing basic life support is an emergency treatment method for SCA. This method can be performed by anyone who is trained. Because this condition can occurs anywhere, such as in a church, it is necessary to prove basic life support training to staff, officers, and youth in those locations. Catholic church St. Mary the Vurgin Queen serves over 3.000 church members in Kebayoran, South Jakarta. As a public facility, SCA can occurs among church members, whether they are participating in religious activities or activities that support religious activities. Therefore, it is important for church staff and youth to be equipped with the ability to recognize the signs of SCA and perform initial treatment before medical personnel arrive or the patient is taken to medical facilities. This activities involves providing training to church staff and youth on recognizing SCA and performing Cardiopulmonary Resuscitation (CPR). It it hoped that, after compliting this training, church staff and youth will be equipped to provide initial treatment for SCA.